Pengaruh Variabel Makroekonomi terhadap Return Saham Indeks Infobank15 - Hesniati Hesniati; Delfina Delfina; Irvin Irvin; Alexander Janio Wijaya; Fionna Quinn; Hardy Winata Lie (Studi Ilmu Manajemen dan Organisasi, 2023)
Purpose: This study analyzes the impact of macroeconomic indicators on banking stock returns. Methodology/approach: This study utilized a quantitative approach with a hypothesis testing method as evidence of the effects of macroeconomic indicators on bank stock returns. The stock index obtained as a sample was the Infobank15 index, consisting of 15 banks in Indonesia over five years, from 2018 to 2022. To examine the relationship in the research model or the impact between variables and to fit the research model, secondary data were used. Data were analyzed using statistical software to implement the data analysis. Results: This study found that the price of the InfoBank15 index is affected either positively or negatively by money supply and exchange rate, respectively, but not by interest rate. Limitations: This research was limited by the short observation period, with limited macroeconomic indicators as the independent variable, and only one index listed in Bursa Efek Indonesia is used as research data.